Development and organization of data bank for automatic drilling tools choosing - Todić, Velimir (Journal of Production Engineering, 1989)
The automatic selection of cutting tools during production and the optimization of technological processes represent important contributions that increase the overall efficiency of technological preparation work. In this paper, the rules and logic for the development, organization, and use of a data bank for the automatic selection of drilling tools are presented.